2014
DOI: 10.1186/s13223-014-0064-7
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of the clinical benefit from acetylsalicylic acid desensitization in patients with nasal polyposis and asthma

Abstract: BackgroundAspirin-exacerbated respiratory disease (AERD), also known as Samter’s triad, is a clinical syndrome which consists of aspirin (ASA) intolerance, chronic rhinosinusitis with nasal polyposis, and intrinsic bronchial asthma (Press Med 119:48-51, 1922). ASA challenge is the gold standard for diagnosing AERD (Curr Allergy Asthma 9:155-163, 2009). The practice of ASA challenge and desensitization in Canada is infrequently utilized, which may explain its omission as a viable therapeutic option in the lates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…showed normalization of olfaction to that of the level of non‐AERD CRS patients as well as improvement of sinonasal symptoms (SNOT‐22 scores) following aspirin desensitization. Additionally, several reports have demonstrated improved QOL in AERD patients following aspirin desensitization, suggesting that this therapy could also potentially impact eating‐related QOL …”
Section: Discussionmentioning
confidence: 99%
“…showed normalization of olfaction to that of the level of non‐AERD CRS patients as well as improvement of sinonasal symptoms (SNOT‐22 scores) following aspirin desensitization. Additionally, several reports have demonstrated improved QOL in AERD patients following aspirin desensitization, suggesting that this therapy could also potentially impact eating‐related QOL …”
Section: Discussionmentioning
confidence: 99%
“…Systemic steroids can be very beneficial in the short term, but may have significant long‐term and short‐term side effects limiting their use. ASA desensitization has been shown to be beneficial for many AERD patients . Previous work has, however, shown that up to 30% of patients report having adverse gastrointestinal side effects secondary to ASA desensitization .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown the efficiency of AD treatment for control of both upper and lower airway disease [19,[23][24][25][26][27][28][29][30][31][32] . In the study by Stevenson et al [23] , 65 AERD patients were treated with a mean aspirin dose of 1,214 mg/day for a mean duration of 3.1 years.…”
Section: Clinical Trials Of Admentioning
confidence: 99%
“…A wide of aspirin dosages (100-1,300 mg/day) were used for the purpose of AD in these studies. There was varying degree of clinical benefit obtained from AD in different studies; some showing benefit for only control of upper airway disease [8,[20][21][22] and some for both upper and lower airway disease [19,[23][24][25][26][27][28][29][30][31][32] . To our knowledge, in only one study, which was carried out on 10 aspirin sensitive asthma patients by using 500 mg aspirin, AD was found ineffective as measured as an improvement on pulmonary function tests and reduced need for systemic corticosteroids [33] .…”
Section: Clinical Trials Of Admentioning
confidence: 99%
See 1 more Smart Citation